LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK ROLE PLAYING UNTUK KEPERCAYAAN DIRI SISWA KELAS XI DI SMA NEGERI 5 KARAWANG - Synthia Tresna; Heris Hendriana; Reza Pahlevi (IKIP Siliwangi, 2022)
This research is motivated by the finding of students who have low self-confidence in school. This study was conducted to determine the implementation, teacher and student responses as well as obstacles in group guidance, which is a form of effort in counseling guidance services to provide students' understanding in increasing self-confidence. This research was conducted with a qualitative descriptive research approach that combines three ways of collecting data, namely observation, interviews and documentation. The research sample is class XI students at SMA Negeri 5 Karawang, namely 1 BK coordinator, 1 BK teacher and 6 students who have low self-confidence. The results showed that the implementation of guidance groups in schools had been carried out well, although there were obstacles in the service delivery process. After being given group service guidance with role-playing techniques, there was a significant change in behavior, especially in the self-confidence of the 6 students compared to before the service was given. So it can be understood that the guidance group service with role-playing techniques is quite effective in increasing students' confidence in school. Keywords: : Self-confidence, Group guidance services, Role Playing Techniques, Students